Changes on the activity of cholinesterase's in an immunomodulatory response of cattle infected by Listeria monocytogenes - Jaguezeski A.M.* (2018)
© 2017 Elsevier LtdThe aim of this study was to evaluate whether Listeria monocytogenes infection alters the activity of cholinesterases in cattle to module their inflammatory response and neurotransmission. Thus, ten male bovines (Holstein) were divided into two groups of five animals each: uninfected (control) and L. monocytogenes infected. Blood samples were collected on days 0, 7 and 14 post-infection (PI) to evaluate the activity of acetylcholinesterase (AChE) in the blood, and seric butyrylcholinesterase (BChE) activity, as well as total protein, albumin, globulin and C-reactive protein (CPR) levels in serum. The AChE activity and acetylcholine (ACh) levels were measured in the central nervous system on day 14 PI, and histopathological analyses were also performed. The infected animals did not show apparent clinical signs of listeriosis, however histopathological alterations were seen in the intestines and spleens. On days 7 and 14 PI, AChE activity in the blood was lower in infected animals, as well the seric BChE activity on day 7 PI. In the cerebral cortex and cerebellum, AChE activity was lower in infected animals compared to the control group, while the ACh levels were higher in the cerebral cortex compared to uninfected animals. Moreover, seric levels of total protein, globulin and CRP were higher in infected animals on days 7 and 14 PI compared to the control group. Therefore, we concluded that acute infection by L. monocytogenes alters the cholinergic system through the reduction of cholinesterase enzymes in the blood, serum and cerebral tissues as an adaptive response to an anti-inflammatory effect in order to increase the ACh levels, an anti-inflammatory molecule with an important role in the host immunomodulation.